Detection of PCB Soldering Defects using Template Based Image Processing Method - Ozturk, Saban; Akdemir, Bayram (International Journal of Intelligent Systems and Applications in Engineering, 2017)
In this study, a predefined template-based image processing system is proposed to automatically detect of PCB soldering defects that negatively affect circuit operation. The proposed system consists of a prototype, a camera, an image processing method and inspect process. The prototype is produced using a plastic material, depending on the focal length of the camera and the PCB size. Image processing step comprises two steps. Firstly, solder joints are determined using Fuzzy C-means clustering algorithm. Then, the center of each joint is determined. In the next step, a joint template is created that contains solder joints information. This joint template contains information about the effects of touching other joints for each joint. In this way, the inspection of soldering defects is getting shorter. Finally, each joint is only inspected for the joints specified in the template. The proposed method is evaluated on 85 real PCB image with 4250 soldering joints.